Kombinasi Metode Multi-Attribute Utility Theory (MAUT) dan Rank Order Centroid (ROC) dalam Pemilihan Kegiatan Ekstrakulikuler - Intan Oktaria (PT. SNN MEDIA TECH PRESS, 2023)
This study aims to select extracurricular activities using the MAUT method using ROC weighting, so that this helps in understanding the consequences of various choices and identifying alternatives that best suit the preferences and goals of decision makers. The results of the study using a combination of MAUT and ROC methods resulted in extracurricular activity recommendations obtained for Karate extracurricular activities with a value of 0.654 getting rank 1. 2nd place was obtained for Futsal extracurricular activities with a value of 0.362, 3rd place was obtained for Scouting extracurricular activities with a value of 0.327.